Research on dual lateral log simulation of shale bedding fractures under different influencing conditions - Wang, Naihui; Li, Kesai; Sun, Jiaqi; Wang, Di; He, Xianhong; Xiang, Zehou; Liu, Hui; Wang, Pan (Frontiers in Energy Research, 2023)
Micro scale fractures play a crucial role in facilitating the migration of oil and gas in low permeability shale reservoirs. However, the identification of such fractures is a complex task. The efficacy of the dual lateral log physical field changes as a means of identifying shale micro fractures remains uncertain. To address this issue, a three-layer shale bedding fracture model was developed using the finite element method and core and conventional logging data from eight wells, which was based on different shale reservoirs within the Yanchang Formation in the Ordos Basin. The present study examines the dual lateral log response characteristics resulting from distinct characteristics of horizontal bedding fractures, with a focus on the response mechanism. The simulation of logging response characteristics of shale and siltstone combination were utilized by core statistical data for verification purposes. The results indicate that under the lithology combination of shale and siltstone, the magnitude of the difference between the resistivity of the filled fracture and the formation resistivity, the greater the formation resistivity of the shale itself, the wider the fracture width, and the greater the difference between the apparent resistivity and the real formation resistivity. Furthermore, the suitable conditions for the detection of shale bedding fracture characteristics by dual lateral log are clarified. In the presence of effective filling, the dual lateral log has the capability to identify shale fractures at the micron scale. The findings of our study establish a theoretical framework for the identification and assessment of shale fractures, and furnish technical assistance for the optimal selection of “sweet spots” within shale reservoirs and the precise evaluation of reservoirs. This study lays a theoretical foundation for the identification and evaluation of shale fractures, and provides technical support for the optimal “sweet spot” selection of shale reservoirs and the accurate evaluation of reservoirs.